Global trends in game-based English language learning: a bibliometric overview - Ismail, Razalina; Abd. Rahman, Siti Fatimah (Global Academic Excellence (M) Sdn Bhd, 2025)
Game-Based Learning (GBL) has gained increasing attention in English language education as an effective way to enhance motivation, engagement and proficiency. However, comprehensive analyses of global research in this area remain limited. This study provides a bibliometric overview of research on GBL in English language learning, focusing on publication trends, influential studies, key contributors and thematic developments. Data were retrieved from the Scopus database using the keywords “Game-Based Learning” and “English Language Learning,” yielding 445 documents published between 2005 and 2025. The dataset was refined using OpenRefine and analyzed with Scopus Analyzer and VOSviewer to examine publication patterns, co-authorship networks, and keyword co-occurrence. Results show a consistent growth of publications with a marked rise after 2020. Taiwan, China, and Malaysia emerged as leading contributors, supported by strong institutional investment in digital pedagogy. Keyword mapping identified recurring themes in pedagogy, motivation, technology integration and vocabulary acquisition. Overall, this study highlights GBL’s increasing prominence in English language education and provides a valuable reference for future research directions.